MODEL DAN PROBLEMATIKA PEMBELAJARAN BAHASA ARAB DI SMA ISLAM KELING JEPARA - Nafisah, Aliyatin (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2012)
Abstract:Â  Whatever the teaching-learning process going on, every teacher should have the policy and strategy to take on the Model of the teaching-learning and get out the record of problems with the teaching-learning process, then search the best solution for them. Especially for the Arabic teacher should have the policy and strategy to take on the Model of the teaching-learning and get out the documentation of challenges with the teaching-learning process, then seek out the best suspension for them. If the Arabic teacher does not do that all, he/she makes self on the place is as far as the Professional Arabic Teacher. the Arabic Teacher in the Tenth Grades of Jepara Keling Islamic Senior High School had do the best way in making the teaching-learning process; His curriculum and Teaching-learning Administration had NR score = 3.35 at level B (High â Good), The Model of the teaching-learning had NR score = 3.55 at level B (High â Good), and the type of Examination and giving the studentsâ score had NR score = 3.47 at level B (High â Good).